The Impacts of Tour de Flores Event for Tourism Development in West Manggarai, Nusa Tenggara Timur - Utan, Febi Marice Erni; Wahyudi, Agustinus Sri; Asmaniati, Fetty (Institut Pariwisata Trisakti, 2017)
This research aims to analyze the impact of Tour de Flores event for tourism development in economic, social and environmental aspects. The 100 respondents are randomly selected from local communities with Slovin formula. Multiple linear regression model is used to analyze the impact of Tour de Flores event on tourism development in West Manggarai. The results of this research have partially proven that tourism development in economic area has a positive impact which is proved by t-test where the value of t count > t table (3,209 > 1,985). Positive impact has shown in environmental as well where the value of t count > t table (2,449 > 1,985) This results means that both variables have a positive impact or H0 is rejected. While the negative relationship or H0 accepted is the impact of tourism development from social where the value of t count < t table (0,314 < 1,985), it means that Tour de Flores event has no social impact on tourism development. Simultaneously, the results of this research show that the three independent variables; tourism development have a positive impact on economic, social and environmental. It is shown by F test that where value of F count > F table (86,723 > 2,699) so that H0 is rejected.